The Effect of Academic Stress and Emotion Regulation on Nomophobia among Undergraduate Students in an Indonesian University - I Komang Adi Asta Gina; Muhammad Shammy Alfian; Tia Rahmania (International Journal of Social Sciences and Humanities, 2026)
This study examined the effects of academic stress and emotion regulation on nomophobia among undergraduate students at an Indonesian university. A quantitative correlational design was employed involving 200 active undergraduate students selected through purposive sampling. Data were collected using the Academic Stress Inventory (ASI), Emotion Regulation Questionnaire (ERQ), and Nomophobia Questionnaire (NMP-Q), and analyzed using multiple linear regression. The findings revealed that neither academic stress nor emotion regulation significantly predicted nomophobia, either individually or simultaneously. The regression model also demonstrated limited explanatory power, indicating that these variables accounted for only a small proportion of variation in nomophobia. These results suggest that nomophobia among university students may be more strongly influenced by other psychological and behavioral factors, such as smartphone usage intensity, fear of missing out (FoMO), social media dependency, and self-control.The study contributes to the nomophobia literature by providing evidence that academic stress and emotion regulation may not constitute primary determinants of nomophobia in higher education settings. This finding highlights the need for future research to explore broader digital behavioral and psychosocial factors in explaining smartphone-related dependence among university students.